Draft Seventh Five Year Plan 1985-90 and Annual Plan 1985-86 Union Territory Administration Dadra and Nagar Haveli - Planning Commission (Planning Commission, 1985)
In order to fully implement the scheme, the Government of India indicated certain norms of staffing. Accordingly the following posts are to sanctioned for Farmers Training Centre.
Union Territory Administration Dadra and Nagar Haveli